Empowering or disempowering? How demographics shape motivational climates and gender equity in Portuguese physical education - Marcelino, Rui (Frontiers in Education, 2026)
Physical education (PE) environments profoundly influence adolescents’ engagement and well-being, yet understanding of how demographic factors shape students’ perceptions of motivational climates remains limited. This cross-sectional study examined 1,166 Portuguese adolescents (M age = 15.2 years) across 12 schools to investigate how gender, extracurricular sports engagement, academic retention, and nationality moderate students’ perceptions of empowering (mastery-focused) versus disempowering (performance-focused) climates in PE. Using the validated Learning and Performance Orientation in Physical Education Classes Questionnaire (LAPOPECQ) and Bayesian analysis, we identified three key findings: (1) Gender equity gaps: Female students perceived performance-oriented climates (both from teachers and peers) as discernably less motivating than male students, suggesting that competitive PE environments may disproportionately alienate female participants. (2) Extracurricular buffering effect: Students engaged in extracurricular sports showed greater tolerance for peer-driven performance climates, possibly through habituation to competitive norms and/or genuine skill develepment. (3) Contextual uniformity: Nationality and academic retention showed negligible influence on climate perceptions, highlighting that climate perceptions are relatively stable across diverse demographic contexts within Portuguese PE settings. By integrating Achievement Goal Theory with demographic heterogeneity, this study advances understanding of how to design equitable PE environments. Practical implications include: (a) prioritizing mastery-oriented climates specifically for female students through targeted pedagogical adjustments; and (b) leveraging quality extracurricular engagement to reframe performance norms constructively rather than as threats. These findings bridge demographic diversity with inclusive pedagogy, offering actionable pathways for educators to foster empowering PE experiences across student populations.